Promoting High Quality Teaching Practices in Higher Education: Lessons Learned from the United States (Economic and Political Thought, 2012)
The article discusses the issues connected with the quality of instruction at the US universities and the ways of raising this level. The authors focus their attention on the faculty members’ experiences and skills.